AN EVALUATION OF TAX AUTHORITIES’ RESPONSE TO TAX NONCOMPLIANCE: EVIDENCE FROM BOTSWANA - Edmore MUNJEYI; Daniel SCHUTTE (Studia Universitatis Babeş-Bolyai Negotia)
This study critically examines the reforms implemented by the Botswana Unified Revenue Service in addressing tax noncompliance, focusing on their influence on taxpayer behaviour. Tax noncompliance, encompassing both evasion and avoidance, poses a significant challenge globally, particularly in terms of impacting revenue collection in developing nations and necessitating an analysis of international responses. Employing a qualitative approach, this research utilised face-to-face interviews and focus group discussions with taxpayers and educators to gauge perceptions of compliance strategies and their effects on voluntary compliance. The findings indicate that reforms by the Botswana Unified Revenue Service have substantially increased tax revenue and increased voluntary compliance, reflecting a shift in taxpayer attitudes from justifying noncompliance to viewing tax payments as moral obligations. The findings underscore the importance of perceived government efficacy and transparency in shaping taxpayer attitudes. This approach highlights the critical role of effective public service delivery in promoting responsible taxpaying behaviour and enhancing overall tax compliance.